Incorporating a Fresh Mixed Annual Ryegrass and Berseem Clover Forage Into the Winter Diet of Dairy Cows Resulted in Reduced Milk Yield, but Reduced Nitrogen Excretion and Reduced Methane Yield - Enriquez-Hidalgo, Daniel; Teixeira, Dayane Lemos; Pinheiro Machado Filho, Luiz Carlos; Hennessy, Deirdre; Toro-Mujica, Paula; Williams, Shaun Richard Owen; Pereira, Fabiellen Cristina (Frontiers in Veterinary Science, 2020)
The winter diet of dairy cows in Mediterranean climate regions is usually a total mixed ration with a base of conserved summer crops such as corn silage and alfalfa hay. However, there is increased labor and financial cost related to this kind of feeding, which could be reduced if fresh forages were used in place of some of the conserved forage in the cow diet. The objective of our study was to evaluate the effect of including fresh mixed annual ryegrass and berseem clover into the diet of dairy cows on milk, nitrogen utilization and methane emission. Twenty-four lactating dairy cows were split into two groups and offered either a diet similar to that usually offered to the cows (CON) or one where a mixture of fresh annual ryegrass and berseem clover was used to partially substitute the corn silage and alfalfa hay in the diet (MIX). Milk yield was recorded automatically, and methane emissions were estimated using the SF6 tracer technique. The MIX diet had lower crude protein concentration (148 vs. 170 g/kg DM) but higher DM digestibility (81.6 vs. 78.6%) than the CON diet. Compared to the cows offered the CON diet, milk yield was reduced when cows were fed the MIX diet (36.4 vs. 31.9 kg/d), but methane emissions (381 vs. 332 g/d) and nitrogen excretion were also reduced (238 vs. 180 g/d). Nitrogen use efficiency was unaffected (30.8%). In addition, milk from cows fed the MIX diet had a fatty acid profile considered to be more beneficial to human health than that of the milk from cows fed the CON diet. Increasing the protein concentration in the MIX diet, either by direct supplementation or increasing the proportion of legume in the mixed herbage, could overcome the reduction on milk and positively affect methane emission and N use efficiency.